The Relationship between Fiber Intake, Physical Activity, and Waist Circumference with Total Blood Cholesterol Levels (Case Study of MTs Teachers in Sukatani District) - El Mahmudiyah, Regietta Neiva Fitriyah; Kurniasih, Ratih; Sefrina, Linda Riski (Jurnal Kesehatan Pasak Bumi Kalimantan, 2024)
Background : The prevalence of hypercholesterolemia in Sukatani District in 2021 was 6.018%. Hypercholesterolemia can be prevented by adequate fiber intake and physical activity so that there is no fat accumulation, especially in the abdomen, so that the waist circumference is average or not at risk of obesity. This study analyzes the relationship between fiber intake, physical activity, and waist circumference with total blood cholesterol levels. Method: This research method uses a cross-sectional design, and the sampling technique uses a purposive sampling technique. Data analysis used the Spearman rank test. Results: The results of this study showed no relationship between fiber intake and physical activity with total blood cholesterol levels (p>0.05), and there was a significant positive relationship between waist circumference and total blood cholesterol levels in MT teachers in Sukatani District (p<0.05).Conclusion : There is no relationship between fiber intake and physical activity with cholesterol levels Keywords:  teacher, fiber intake, physical activity, waist circumference, total cholesterol